2018
DOI: 10.1080/02770903.2018.1455860
|View full text |Cite
|
Sign up to set email alerts
|

The current prevalence of asthma, allergic rhinitis, and eczema related symptoms in school-aged children in Costa Rica

Abstract: The prevalence of asthma showed a significant decrease compared to previous studies. However, there was an unexpected high prevalence of rhinitis. Exposure to acetaminophen and antibiotic during the first year of life was highly associated with asthma symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 51 publications
3
21
2
3
Order By: Relevance
“…With the development of social economy, various allergic diseases are increasing. 23 The prevalence of AR has increased significantly, especially in industrialized or developed countries with higher living standards. T-helper type 1 (Th1) and Th2 cytokines interact to participate in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of social economy, various allergic diseases are increasing. 23 The prevalence of AR has increased significantly, especially in industrialized or developed countries with higher living standards. T-helper type 1 (Th1) and Th2 cytokines interact to participate in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Em Ijuí a rinite é mais elevada que a descrita, está presente em 87% dos escolares com asma, enquanto que em Porto Alegre está abaixo da relatada pela literatura, acorrendo em 58,8% dos casos. As frequências encontradas para atopia estão elevadas em ambos os locais de estudo, em Ijuí ocorre em 81,4% dos escolares com asma, e em Porto Alegre afeta 63,5%, enquanto que estudos relatam taxas de atopia entre 42,6% e 50,4% [21,22].…”
Section: Discussionunclassified
“…Em Porto Alegre essa associação ocorre em 84,3% dos casos, e é maior ainda em Ijuí, 93,5%. Enquanto isso, a literatura descreve essa situação em apenas 22,6% dos asmáticos [22].…”
Section: Discussionunclassified
“…It should be noted that the present study found a higher consumption of antihistamines than that reported in similar studies conducted in other countries (11,12,14). This may be related to the prevalence of rhinitis and allergies in the Costa Rican population (42.6%), as well as environmental and geographical factors (17). In Costa Rica, the medications with the highest prevalence of poisoning are paracetamol, antihistamines, and ibuprofen (16,18).…”
Section: Discussionmentioning
confidence: 99%